Pomiędzy kryzysem, a szansą - koncepcja rezyliencji w rodzinie - Dzierzyńska-Breś, Sonia (Kultura-Społeczeństwo-Edukacja, 2025)
The purpose of this article is to present the concept of family resilience .The present study aims to shed light on the subject’s comprehension of the systemic paradigm, while concomitantly underscoring the pivotal role that the family environment and its concomitant processes play in its establishment. A multi-tude of factors, including losses, traumatic events, highly stressful living conditions, and rapid changes in civilization, have been demonstrated to exert a detrimental effect on the entire network of family relation-ships. These phenomena are posited to challenge the conventional notion of the family as a functional system. The selection of coping strategies and the subsequent adaptation and adjustment of all family members in a crisis situation are primarily influenced by the fundamental processes within the family unit. The fundamental question that researchers in this field seek to address is as follows: What factors enable certain families to overcome adversity, thereby enhancing their functionality and resilience, while others succumb to dissolution or deterioration?